Rafflesia Nursery Centre / Ayu Zulaika Athanazir ... [et.al.] - Athanazir, Ayu Zulaika; Zainorin, Nia Nadhira; Romzi, Nurul Athirah; Rosdi, Roszie (2012)
Our company is called Rafflesia Nursery Centre. Our nature of business is education. We provide an early education for four-year-old children and below to expand their potential to being the next great generation through holistic education. Rafflesia Nursery Centre is Partnership Company consists of four members which is General Manager, Marketing Manager, Financial Manager while Administration Manager and Operational Manager are handled by one person. Nia Nadhira binti Zainorin will be the leader of the company which is the General Manager of Rafflesia Nursery Centre while Nurul Athirah binti Romzi as our Marketing Manager, Roszie binti Rosdi will be Administration Manager and also will be responsible to manage operational section and Ayu Zulaika binti Athanazir is our Financial Manager.